The effect of vigorous aerobic and standard anaerobic exercise testing on GH-IGF-1 secretion in adult females - Rakover, Noa; Nemet, Dan; Meckel, Yoav; Pantanowitz, Michal; Zaken, Sigal Ben; Eliakim, Alon (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Exercise-associated effects on the GH→IGF-1 axis were studied, mainly following aerobic exercise. Material and Methods. The effects of laboratory vigorous aerobic (10-min treadmill run at 85% of peak VO2) and standard all-out anaerobic (30 s Wingate anaerobic test- WAnT) tests on the GH→IGF-1 axis were determined in 12 healthy active females (24-34 years). The tests were performed in random order. Blood samples for GH and IGF-1 were collected before and 20, 30, 40 and 60 minutes after the beginning of each exercise test. Both tests were associated with significant increases in GH. Results. Peak GH was higher following the WAnT (11.0 ｱ 8.3 vs. 7.5 ｱ 7.3 ng/ml, respectively) but this difference was not statistically significant. However, the GH area under the curve (AUC) was significantly greater in the anaerobic test as compared with the aerobic test. Only the WAnT was associated with a significant increase in IGF-1 levels (from 177.8 ｱ 47.2 to 198.8 ｱ 56.2, p < 0.02). However, no significant differences were found in peak IGF-1and IGF-1 AUC following both tests. Vigorous aerobic and standard all-out anaerobic laboratory tests led to significant GH increases in the same female individuals. GH and IGF-1 responses were greater following the WAnT. Conclusions. GH-IGF-1 changes may be used to gauge exercise intensity, not only following aerobic but also anaerobic exercise.Introduction. Exercise-associated effects on the GH→IGF-1 axis were studied, mainly following aerobic exercise. Material and Methods. The effects of laboratory vigorous aerobic (10-min treadmill run at 85% of peak VO2) and standard all-out anaerobic (30 s Wingate anaerobic test- WAnT) tests on the GH→IGF-1 axis were determined in 12 healthy active females (24-34 years). The tests were performed in random order. Blood samples for GH and IGF-1 were collected before and 20, 30, 40 and 60 minutes after the beginning of each exercise test. Both tests were associated with significant increases in GH. Results. Peak GH was higher following the WAnT (11.0 ｱ 8.3 vs. 7.5 ｱ 7.3 ng/ml, respectively) but this difference was not statistically significant. However, the GH area under the curve (AUC) was significantly greater in the anaerobic test as compared with the aerobic test. Only the WAnT was associated with a significant increase in IGF-1 levels (from 177.8 ｱ 47.2 to 198.8 ｱ 56.2, p < 0.02). However, no significant differences were found in peak IGF-1and IGF-1 AUC following both tests. Vigorous aerobic and standard all-out anaerobic laboratory tests led to significant GH increases in the same female individuals. GH and IGF-1 responses were greater following the WAnT. Conclusions. GH-IGF-1 changes may be used to gauge exercise intensity, not only following aerobic but also anaerobic exercise.
Keywords: laboratory testing; females; power output; endurance activity